Estatística: uma abordagem diferenciada no ensino médio - Flôres, Gilciane de Quevedo (2019)
The objectives of this work are the elaboration, application and validation of a didactic sequence. This sequence can be contribute to the teaching and learning of the content of Statistics in High School. Didactic Engineering were used as a methodology. Initially, a study was carried out on standardization and curricular guidelines for the teaching of Statistics in Basic Education. Following, the main definitions for the study of Statistics in High School were presented, as well as some examples to illustrate such definitions. Afterwards, it is discussed the Didactic Engineering as a guiding methodology of the didactic sequence. Consequently, the goal was to carry out research inside and outside the school, applying the knowledge acquired on Statistics to simplify and analyze the data collected by the student researches. As a conclusion, an evaluation is presented, recording the objectives that have been achieved and the aspects that need to be improve in the proposal.